BANYUWANGI SONG: THE USING CULTURE IN SECONDARY ORALITY - Heru S.P. Saputra; Titik Maslikatin; Edy Hariyadi (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
This study aims to discuss the lyrics of the Basanan song by B.S. Nurdian, sung by Catur Arum and posted on the Youtube channel, interprets the Using (Banyuwangi) culture in the context of secondary orality. This study uses a qualitative method with an oral approach to analyze the formula and oral characteristics in the text of the Basanan song. The results showed that the text of the Basanan song contained the tautotes repetition formula, mesodiplosis repetition formula, anaphora repetition formula, and showed formulaic expressions. The language characteristics in the Basanan text are the characteristics of spoken language because they are additive and aggregative. The substance of the text of the Basanan song reflects the cultural condition of the Using community. In the development of media, many Using people use social media to express artistic expression and for financial gain. The significance of the dynamics of civilization for the Using people is that the primary oral language has now entered the secondary oral language and has become a popular cultural product for the Using people, Banyuwangi, reflecting the dynamics of their civilization.